Effect of silica fume on engineering properties of expansive soil. (2020) - Singh, Pratyasha; Kumar Dash, Hemanta; Samantaray, Sandeep
Abstract: Rapid growth of urbanization and industrialization has led to drastic industrial waste which has become a giant threat to our nature. Minimizing industrial waste now days posing a serious problem in the present scenario. To tackle the problem now a days many innovative and non-traditional researches on waste utilization is gaining importance. The primary purpose of this experimentation is to evaluate the suitability of using the low-cost material i.e. Silica fume as a soil stabilization material. This project work presents the study of expansive soil stabilized with silica fumes which was assembled from an idyllic area named Kalatunga located in Kendrapada district of Odisha state. Soil stabilization was done with various percentages of silica fumes (10 to 100%). The differential free swell (DFS), Atterberg's limits, standard proctor compaction, california bearing ratio (CBR), unconfined compressive strength (UCS) test and unconsolidated un-drained triaxial (UU) test were carried out on natural and silica fume stabilized soils. Results display that addition of SF scales down the DFS. The compaction curves point out that addition of silica fume results in an increase in optimum moisture content (OMC) and decrease in maximum dry density (MDD). The addition of stabilizers (i.e. silica fumes) escalates the cohesion (C) values in UCS along with an in increase in cohesion and angle of shearing resistance (Ø) in UU triaxial test demonstrating progress in the strength properties of soil.